Fabrication of gelatin/carbon nanocomposite for human tissue adhesive - Rungsarit Koonawoot (2018)
Successful human tissue adhesives depend on sure parameters which cannot be matched by any one adhesive. In this work, the novel human tissue adhesive is fabricated from gelatin and coconut shell carbon nanopowder composite. Characteristics of the carbon powder and the product samples were then investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM). Mechanical characterization and tissue adhesive bonding test of the final product were also performed. © (2010) Trans Tech Publications.